EVALUATION OF DRUG DOSES CALCULATION SKILLS OF REGISTERED NURSESWORKING IN TERTIARY CARE HOSPITAL OF RAWALPINDI: AN INTERVENTIONAL STUDY (The Research of Medical Science Review, 2024)
Medication errors due to incorrect dosage calculations are a significant concern in healthcare, potentially leading to adverse patient outcomes. This study aimed to assess the effectiveness of a structured educational intervention on improving nurses' drug dosage calculation skills in a tertiary care hospital. Enhancing these skills is crucial for patient safety and quality care, A quasi-experimental design was used with a sample of 220 nurses in a tertiary care setting. Participants completed a pre-intervention test assessing dosage calculation skills, followed by a structured training session on dosage calculations. A post-intervention test was conducted immediately after the training to evaluate the impact of the intervention. Data were analyzed using paired t-tests to compare pre- and post-intervention scores, The results showed a significant improvement in nurses' calculation accuracy and confidence following the educational intervention. The average post-intervention test scores were significantly higher compared to pre-intervention scores (p < 0.05), indicating the effectiveness of the training session in enhancing dosage calculation skills, The study concludes that structured educational interventions can effectively improve nurses' drug dosage calculation skills, thereby potentially reducing medication errors. Continued support, periodic refresher training, and additional decision aids are recommended to maintain competency in dosage calculations and enhance patient safety in clinical settings.